Examining the practical viability of internationally recognised standards in preventing the movement of money for the purposes of terrorism: A crime script approach. Issue 2 (2nd May 2017) - Gilmour, Nicholas; Hicks, Tristram; Dilloway, Simon
Abstract : Purpose: The purpose of this paper is to examine – using crime script analysis – the practical effectiveness of internationally endorsed and universally recognised counter-terrorism financing (CTF) standards in preventing the movement of money for the purposes of terrorism. The paper does not seek to examine the originating circumstances of terrorist finances or how laundered value is assigned. Design/methodology/approach: Preliminary evaluation focuses on the discrepancies between the practices of money laundering and terrorist financing. Following an introduction to crime scripts, internationally endorsed anti money laundering (AML)/CTF practices are discussed to identify the process used to trace, prevent and limit money laundering and terrorist financing. Several terrorist financing case studies are then aligned to the process of crime script analysis to determine whether existing AML/CTF practices are effective in preventing terrorist financing. Findings: The AML model "Placement, layering, integration" is only relevant to CTF in the comparatively rare cases when the origin of the money is crime. This creates a false sense of security through over reliance on AML/CTF for CTF purposes. A crime script approach can be applied to terrorist finance, but it is currently hindered by insufficient reporting of low level financing of terrorists, their addresses and associates. Law enforcement make insufficient use of financial intelligence – as a routine practice – in their crime and terrorist investigations; they have not adopted parallel investigation as a routine approach and consequently remain largely unconnected with the AML/CTF regime. Practical implications: Utilising terrorist financing case studies, this paper identifies that existing AML/CTF international standards and practices are not adequate for controlling the movement of funds for financing terrorism because of the lack of focus on a specific script that aligns to known terrorist finance methodologies. While the paper identifies that existing AML/CTF international standards are thorough, the process underpinning the financing of terrorism is too dissimilar to the process of money laundering, namely, placement, layering, and integration, to support practices associated with terrorism prevention and detection. Originality/value: This paper provides an examination of the practicalities behind the countering of terrorist financing from a compliance and investigative perspective. The paper is of interest to those involved in policy, compliance and investigations associated with terrorist financing.